Quality of life of psoriatic patients – modulatory variables - Gawlik, Marta Maria; Topczewska, Barbara; Kurpas, Donata (Family Medicine & Primary Care Review, 2016)
Background. In recent years, there has been increasing interest in the quality of life (QoL) of patients with dermatological conditions. The problem of the stigma associated with some dermatological conditions has been discerned, as patients suffering from chronic dermatoses tend to perceive themselves in a specific way and to assess their QoL as very low. Objectives. Identification of factors that influence the QoL of patients with psoriasis. Material and methods . This survey-based quantitative research was carried out at the dermatology ward of the Voivodeship Specialist Hospital, Research and Development Centre in Wroclaw, Poland. The study involved 130 adult patients with a diagnosis of psoriasis, of whom 56.92% (74) were women. The research instruments used were the Dermatology Life Quality Index (DLQI), the Hospital Anxiety and Depression Scale (HADS), and a questionnaire of the authors’ own design. Results . The median for disappearance of psoriatic patches after hospitalization was 5 (range: 0–10). The median for the remission duration was 3 months (range: 0.25 to 24). 61.54% (80) of those surveyed reported improvement in their psoriasis treatment as a result of regular check-ups at the outpatient dermatology clinic. Disease-related anxiety and QoL were determined by marital status and the level of education. Older patients more often had symptoms of depression, according to HADS. Higher DLQI scores correlated with higher HADS-A and HADS-D scores. Conclusions . Psoriasis has significant effects on patients’ mental states and social functioning. The most serious and unpleasant symptoms are pruritus and skin lesions on the uncovered parts of the body. The patients with the highest risk of a lower QoL are the elderly; those living alone (single or widowed); those with secondary, vocational, or no education; and those with symptoms of anxiety or depression.